2004
DOI: 10.1111/j.1432-2277.2004.tb00416.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the public attitudes towards organ donation in a Turkish community and of the changes that have taken place in the last 12 years

Abstract: In 1990 we carried out a survey on public attitudes toward organ donation in a Turkish community. We repeated this study 12 years later in order to evaluate the changes that had taken place in the meantime. Using the same questionnaire and method, we repeated the study in a different part of the city with similar socio-economic characteristics as in the former area, which had in the meantime ceased to be our research and training area. The 983 participants were chosen by a random stratified method. Of those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 12 publications
(11 reference statements)
6
32
0
4
Order By: Relevance
“…This is consistent with previous studies in Saudi Arabia [23,24,30,31] and other Islamic countries [25,26,32-35]. In Saudi Arabia, a 1991 study found that 53% of responders either signed a kidney donor card or expressed willingness to do so [30], a 1996 study found that 67% were willing to donate [23], a 2005 study found that 42% agreed to donate [24], and a 2009 study found that 71% were willing to donate [31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies in Saudi Arabia [23,24,30,31] and other Islamic countries [25,26,32-35]. In Saudi Arabia, a 1991 study found that 53% of responders either signed a kidney donor card or expressed willingness to do so [30], a 1996 study found that 67% were willing to donate [23], a 2005 study found that 42% agreed to donate [24], and a 2009 study found that 71% were willing to donate [31].…”
Section: Discussionsupporting
confidence: 93%
“…In Saudi Arabia, a 1991 study found that 53% of responders either signed a kidney donor card or expressed willingness to do so [30], a 1996 study found that 67% were willing to donate [23], a 2005 study found that 42% agreed to donate [24], and a 2009 study found that 71% were willing to donate [31]. A 2005 study in Qatar, found that 37.8% of Qataris and 32.8% of non-Qataris were willing to donate [32], a 2009 study in Pakistan found that 62% expressed a motivation to donate [26], a 2006 study in Nigeria showed that 30% expressed a willingness to donate [33], a 2009 study in Malaysia showed that 41% reported that they have registered to be organ donors or indicated willingness to donate [34], and in Turkey, a 2002 study found that 57% were willing to donate [35] and a 2009 study of students from the faculty of theology found that 24% were willing to donate their organs and 57% were undecided [25]. …”
Section: Discussionmentioning
confidence: 99%
“…4 Another study conducted on 938 participants from Ertugrulgazi, in western Turkey, also indicates that increased education was positively related to awareness of organ donation. 5 In addition, another study done in Nigeria also suggests that knowledge about organ donation and willingness to become organ donors is higher among those with a tertiary level of education than it is among those with a pretertiary level. 6 This paper is a result of a survey that was done to assess the views of better-educated persons in Malaysia with the hope of identifying factors that influence educated Malaysians (people with most access to information) to donate or not to donate their organs.…”
Section: Introductionmentioning
confidence: 99%
“…Educational factors play an important role in countering this. H. Bilgel, G. Sadikoglu and N. Bilgel (2006) states that in Turkey, many factors can influence the attitudes of people on the organ donation such as age, religion and education.…”
Section: Phenomenonmentioning
confidence: 99%